Removal of Zinc and Cadmium by Activated Carbon Adsorption - Gupta, Suruchi; Bhatnagar, Mridula (Asian Journal of Chemistry, 2010)
The possibilities of removal of zinc and cadmium have been investigated using activated carbon. The experiments were conducted with soil solutions containing zinc and cadmium. Considerable amounts of zinc and cadmium are removed by powdered activated carbon from soil solutions. The amount of these metals removed strongly depends upon the pH of the solution.